The Effect of Work Stress on Marketing Employee Performance: Study at PT. Bumi Aksara - Musa, Chalid Imran (PT Maju Malaqbi Makkarana, 2024)
Numerous aspects must be taken into account, including work stress, in order for an employee to provide quality work results. Employees are undoubtedly negatively impacted by job stress because it lowers productivity and makes it more likely that the organization won't meet its objectives. The goal of this study is to determine the level of work stress that employees experience, their current work results, how work stress itself affects performance, and how much of an impact the level of work stress has on the work performance of employees of PT. Bumi Aksara marketing department. A quantitative deskriptive technique was used in this research. According to research based on 30 respondents, work-related stress has an impact on employee performance. The regression analysis's findings are Y=6,597+0,649X. This shows that a one-point increase in workplace stress will result in a 0,649-point increase in employee performance. Employee performance was impacted by work-related stress by 62,6%; the remaining effects accounted for the remaining percentage. Even though the employees of PT. Bumi Aksara marketing department execute well, the business may still get the best out of them